Community Perceptions and Adaptation in Smoke Free Zone Policy: A Qualitative Case Study in Kendari City - Anas, Adhe Sofyan; Alchamdani; Syam, Sadli; Arwan; Firmansyah (Medicor : Journal of Health Informatics and Health Policy, 2024)
The implementation of Smoke Free Zone (SFZ) policies is a critical public health strategy, especially in densely populated urban settings. This study examines how residents of Kendari City, Indonesia, perceive and adapt to SFZ regulations enacted under Local Regulation No. 4 of 2019. Specifically, it explores community understanding, experiences, and behavioral responses to smoking restrictions in public spaces. A qualitative case study approach was employed, utilizing purposive sampling to select twelve informants from various socio economic backgrounds. Data were gathered through semi structured interviews, non-participant observation, and field documentation. Thematic analysis was used to interpret interview transcripts and observational notes. The findings show limited community understanding of SFZ boundaries, with common misconceptions about designated areas. While most residents support the policy’s intent, cultural norms and perceived lack of authority reduce active enforcement. Structural barriers such as economic hardship, nicotine addiction, and weak public communication further constrain compliance. Nonetheless, positive adaptations are evident, including peer influence, community-led signage, and selective smoking avoidance in public spaces. These behaviors reflect the role of informal networks and increasing health awareness. The study concludes that SFZ policy effectiveness is contingent on interdisciplinary approaches, inclusive communication, and localized community engagement. Rather than relying solely on top down regulation, integrating health messaging, urban design, and community leadership is essential for fostering sustained compliance. The insights from Kendari highlight the potential of participatory and culturally responsive strategies in strengthening public health policies.